Nutritional, Antioxidant and Structural Properties of Rusk Developed From Wheat–Bambara Groundnut (Vigna subterranean) Flour - Shonisani Eugenia Ramashia; Rilwele Calmon Sikhipha; Gbeminiyi Olamiti; Mpho Edward Mashau (Legume Science)
ABSTRACT Bambara groundnut (BGN) is an underutilised legume that has been utilised in bakery products to enhance the protein and crude fibre content. The aim of this study was to evaluate the effect of BGN flour on the nutritional, antioxidant and microstructural properties of wheat flour rusks. Five formulations of rusks were produced by adding different levels (0%, 5%, 10%, 15% and 20%) of BGN flour. Increasing BGN flour from 0% to 20% decreased bulk density, water and oil absorption capacity, swelling capacity and cold paste viscosity of the wheat flour. Nonetheless, addition of BGN flour increased the hot paste viscosity of flour samples ranging from 1132 to 1162.67 cP. It was observed that the inclusion of BGN flour increased the ash, fat, protein, crude fibre content, polyphenols and antioxidant activity of wheat flour and rusk, while moisture, carbohydrate and energy content decreased. As the amount of BGN flour increased, darkening in colour of the wheat flour and rusks were observed. Distinct functional groups exhibited peaks in flour and rusk with increased in percentages of BGN flour. The addition of BGN flour decreased physical properties of the rusks such as loaf volume and specific volume, hardness and fracturability. Furthermore, inclusion of BGN flour altered the microstructural properties of the rusks. Overall, this study provides valuable insights into the sustainability and application of BGN flour in bakery products.